Google, the company that Europe loves to hate - Codina, Lluís (Anuario ThinkEPI, 2015)
Some considerations We offer some thoughts about the apparent current climate of opinion and criticism against Google, which in the author´s opinion is not based on substantiated facts or analysis, but on perceptions, not necessarily based on any rationale. According to the author, this is a periodically repeated style of reaction against some outstanding company (formerly Apple, IBM, Microsoft, and before that Xerox, etc.). Hates, loves and indifference in this area do not seem to obey logical rules but rather some kind of reasoning that perhaps may be linked to Europe´s inability to lead in technological issues.